2017
DOI: 10.1039/c7tb00344g
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid-modified chitosan nanoparticles for Cu2+ chelation to suppress CuO nanoparticle cytotoxicity

Abstract: Chitosan nanoparticles grafted with amino acids suppress the cytotoxicity of engineered nanoparticles by chelating intracellularly released metal ions and scavenging intracellular reactive oxygen species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…In NPs-based drugs discovery, for example, confirmation of NPs potency and their side effects in vitro are important, because in vitro experiments can sometimes provide potential outcomes with drug candidate agents that are relevant to in vivo conditions. 8 To candidate NPs for anticancer activity, their side effects against healthy targets such as the protein structure [9][10][11][12] and cell lines [13][14][15] should be assessed. It has been well documented that plasma proteins like albumins are adsorbed on the NP surfaces as the protein corona in the biological system.…”
Section: Introductionmentioning
confidence: 99%
“…In NPs-based drugs discovery, for example, confirmation of NPs potency and their side effects in vitro are important, because in vitro experiments can sometimes provide potential outcomes with drug candidate agents that are relevant to in vivo conditions. 8 To candidate NPs for anticancer activity, their side effects against healthy targets such as the protein structure [9][10][11][12] and cell lines [13][14][15] should be assessed. It has been well documented that plasma proteins like albumins are adsorbed on the NP surfaces as the protein corona in the biological system.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to cells being physically covered by the nanoparticles and subsequently cell death. The presence of high nanoparticle populations will easily agglomerate at the cell surface and consequently influence the absorption of nutrients and gaseous exchange and thus confer toxicity to cells [ 84 ] Additionally, previous studies have shown that CNP has no any significant cytotoxicity toward several cell lines such as HepG2 human liver cancer cell line, RAW 264.7 mouse macrophage, as well as the A549 cell lines [ 85 , 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…CS NPs modified with the amino acids lysine and glutamic acid were designed to chelate copper ions and prevent cytotoxicity and ROS production of CuO NPs. Despite the PC formed, which predominantly contained albumin, the chelating efficiency was not significantly reduced [57] . However, PC may not be created at all.…”
Section: Interaction Between Polysaccharide‐based Nanoparticles and Tmentioning
confidence: 89%